METODE BERNYANYI DALAM MENINGKATKAN PENGUASAAN MUFRADAT PADA PESERTA DIDIK SEKOLAH DASAR - Maemunah Maemunah; Isra Hayati Darman; Syaipuddin Rittongga (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
The purpose of this study was to examine students’ vocabulary mastery through the use of the singing method. This research employed a qualitative descriptive approach, involving fifth-grade students and Arabic language teachers as informants. Data were collected through classroom observations, in-depth interviews, and documentation. The findings indicate that the singing method contributes positively to improving students’ vocabulary mastery. Low levels of interest and learning motivation were identified as major obstacles in the vocabulary learning process. The implementation of the singing method created a more enjoyable learning atmosphere, increased student participation, and facilitated easier vocabulary recall and comprehension. In addition, the repetitive lyrics and rhythmic patterns in songs help strengthen students’ memory retention, enabling vocabulary to be stored more effectively in long-term memory. Therefore, the singing method can serve as an effective alternative learning strategy to enhance vocabulary mastery among fifth-grade elementary school students.